Cost-effectiveness of screening for hepatitis C virus: a systematic review of economic evaluations. Issue 9 (6th September 2016) - Coward, Stephanie; Leggett, Laura; Kaplan, Gilaad G; Clement, Fiona
Abstract : Objectives: With the developments of near-cures for hepatitis C virus (HCV), who to screen has become a high-priority policy issue in many western countries. Cost-effectiveness of screening programmes should be one consideration when developing policy. The objective of this work is to synthesise the cost-effectiveness of HCV screening programmes. Setting: A systematic review was completed. 5 databases were searched until May 2016 (NHSEED, MEDLINE, the HTA Health Technology Assessment Database, EMBASE, EconLit). Participants: Any study reporting an economic evaluation (any type) of screening compared with opportunistic or no screening for HCV was included. Exclusion criteria were: (1) abstracts or commentaries, (2) economic evaluations of other interventions for HCV, including blood donors screening, diagnosis tests for HCV, screening for concurrent disease or medications for treatment. Primary and secondary outcome measures: Data extraction included type of model, target population, perspective, comparators, time horizon, discount rate, clinical inputs, cost inputs and outcome. Quality was evaluated using the Consolidated Health Economic Evaluation Reporting Standards checklist. Data are summarised using narrative synthesis by population. Results: 2305 abstracts were identified with 52 undergoing full-text review. 30 papers met inclusion criteria addressing 7 populations: drug users (n=6), high risk (n=5), pregnant (n=4), prison (n=3), birth cohort (n=8), general population (n=5) and other (n=6). The majority (77%) of the studies were high quality. Drug users, birth cohort and high-risk populations were associated with cost-effectiveness ratios of under £30 000 per quality-adjusted-life-year (QALY). The remaining populations were associated with cost-effectiveness ratios that exceeded £30 000 per QALY. Conclusions: Economic evidence for screening populations is robust. If a cost per QALY of £30 000 is considered reasonable value for money, then screening birth cohorts, drug users and high-risk populations are policy options that should be considered.